2020
DOI: 10.1186/s13054-020-03358-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the cuff leak test in adults in predicting post-extubation airway complications: a systematic review and meta-analysis

Abstract: Background Clinical practice guidelines recommend performing a cuff leak test in mechanically ventilated adults who meet extubation criteria to screen those at high risk for post-extubation stridor. Previous systematic reviews demonstrated excellent specificity of the cuff leak test but disagreed with respect to sensitivity. We conducted a systematic review and meta-analysis to assess the diagnostic accuracy of the cuff leak test for predicting post-extubation airway complications in intubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…For example, the patient considered at risk of supraglottic or glottic airway edema might be assessed with a cuff leak test. 221,[226][227][228] In a recent systematic review, the authors concluded that the absence of a cuff leak in an at-risk patient is associated with post-extubation stridor or need for re-intubation, but the presence of a leak does not necessarily rule out the occurrence of stridor or need for re-intubation. 228 Further assessment of the at-risk patient can occur by indirect visual evaluation of the glottis and supraglottic area using a VL 229 or FB before emergence from anesthesia or sedation begins.…”
Section: The At-risk Tracheal Extubationmentioning
confidence: 99%
“…For example, the patient considered at risk of supraglottic or glottic airway edema might be assessed with a cuff leak test. 221,[226][227][228] In a recent systematic review, the authors concluded that the absence of a cuff leak in an at-risk patient is associated with post-extubation stridor or need for re-intubation, but the presence of a leak does not necessarily rule out the occurrence of stridor or need for re-intubation. 228 Further assessment of the at-risk patient can occur by indirect visual evaluation of the glottis and supraglottic area using a VL 229 or FB before emergence from anesthesia or sedation begins.…”
Section: The At-risk Tracheal Extubationmentioning
confidence: 99%
“…However, intubation can be associated with serious complications such as laryngeal edema that may result in a life‐threatening upper airway obstruction postextubation. A recent systematic review and meta‐analysis of 4493 patients in 28 observational studies reported that approximately 9% of all patients will develop postextubation laryngeal edema, and 3% of patients will require reintubation for an upper airway obstruction 1 . Reintubation has been associated with significant morbidity and mortality 2‐7 …”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of a CLT is debatable. To date, three systematic reviews and meta‐analyses have examined the diagnostic accuracy of the CLT 1,9,10 . All found that a failed CLT was a predictor of laryngeal edema but may not predict reintubation 1,9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laryngeal edema and post-exubation stridor are related to reintubation, and the incidence of postextubation stridor is reported to be 2-26% [1]. The cuff leak test (CLT) is conducted to predict the presence of laryngeal edema and post-extubation stridor [2,3], and the sensitivity and speci city of the CLT were reported as 0.62 and 0.87 [3], respectively. The CLT can sometimes be falsely positive.…”
Section: Introductionmentioning
confidence: 99%